Home Electrical Lighting System: Remotely Control and Power Monitoring - Muhammad Aiman Ahmad Tulus; Abdul Sukor, Jumadi (Progress in Engineering Application and Technology, 2022)
Life is becoming simpler and easier in many areas as a result of the development of automation technologies. Automatic methods are increasingly becoming favourable over manual ones in today’s society. With the fast rise in the number of internet users over the last decade, the internet has become an integral part of everyday life, and the Internet of Things (IoT) is the most recent and most promising internet technology. An expanding network of common objects ranging from industrial machines to consumer products that can exchange information and perform tasks while you are engaged in other activities is known as the Internet of Things. IoT enabled Wireless Home Automation System (WHAS) is a system that uses computers or mobile devices to control basic home functions and features automatically through the internet from any location in the world. A smart home is also referred to as an automated home when it is controlled remotely through the internet. Its purpose is to save electric power as well as human energy. The home automation system varies from previous systems in that it allows the user to control the system from any location in the globe by using an internet connection to connect to the system.